2014
DOI: 10.1007/s00037-013-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

The NOF Multiparty Communication Complexity of Composed Functions

Abstract: Abstract. We study the k-party 'number on the forehead' communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…See also the survey [45]. Both methods have since been studied in the two-party setting [35,43,48] and also the multiparty setting [33,3,11,50,51,38].…”
Section: Main Structural Result: Junta Theoremmentioning
confidence: 98%
“…See also the survey [45]. Both methods have since been studied in the two-party setting [35,43,48] and also the multiparty setting [33,3,11,50,51,38].…”
Section: Main Structural Result: Junta Theoremmentioning
confidence: 98%
“…See also the survey [She08]. Both methods have since been studied in the two-party setting [LZ10,RS10,She11b] and also the multiparty setting [LS09b,AC08,Cha08,She12b,She14,RY15].…”
Section: Main Structural Result: Junta Theoremmentioning
confidence: 99%
“…In this section, we prove essentially an exp − √ N/4 k upper bound on the discrepancy of the GHR N k function where the first player gets N input bits. This gives us an exp −n Ω (1) upper bound on the discrepancy if k ≤ ε log(N) for any constant 0 < ε < 1/4. Goldmann et al [17] showed that when k = 2, if there is a low cost one-way protocol for GHR N 2 , then it must have low advantage.…”
Section: A Discrepancy Upper Bound For the Multiparty Ghr Functionmentioning
confidence: 97%
“…for some constant ε > 0 to give us a discrepancy upper bound of exp −n Ω (1) . For notational convenience, we may switch between the notations Ex and Ex∼µ X from now on.…”
Section: Fact 33 (Law Of Total Expectation)mentioning
confidence: 99%
See 1 more Smart Citation